Bee-Keeping.
Shelf no.
The baobab tree grows mostly in the coastal belt.It does not have a dense foliage and mot of the time the breaches appear quite bare.There is a legend that God plante dit upside down,since the branches look mor e like roots.A beehive (hallowed out trunk,probably of a baobab,which i spithy) rests in the branches of this tree.At the foot of the tree is t he skull of a steer ,to keep off poaches.Skulls,animals and human, have been much used as such warnings in the past,but are infrequently seen nowadays.Makindu.
AR/MAK PHOTOS/21/7
English
Keywords: Photos of Kenya